2014
DOI: 10.1071/mf13330
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the whale shark (Rhincodon typus) in the north-western Pacific

Abstract: This study estimated age and growth of the largest extant fish, the whale shark (Rhincodon typus) by counting vertebral band pairs from 92 specimens comprising 43 males (2.68–9.88 m total length [TL]), 30 females (1.60–7.02 m TL), and 19 unsexed individuals (2.83–6.67 m TL) taken by Taiwanese commercial fisheries during 2001–06. Growth band pairs up to 25 and 42 were counted for a 6.38-m TL female and a 9.88-m TL male, respectively. Using marginal increment ratio and centrum edge analysis, band pairs were post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 48 publications
4
38
2
Order By: Relevance
“…While these growth rates are of similar magnitude to estimates for wild R. typus , typically in the 20 to 40 cm/yr range (Hsu et al. , Norman and Morgan ), higher rates could be expected due to better nutrition in the aquarium. Indeed, growth as high as 75 cm/yr was observed for the maturing #3 in the present study, while another captive R. typus in Taiwan (67 cm/yr) also grew markedly faster than wild averages (Leu et al.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…While these growth rates are of similar magnitude to estimates for wild R. typus , typically in the 20 to 40 cm/yr range (Hsu et al. , Norman and Morgan ), higher rates could be expected due to better nutrition in the aquarium. Indeed, growth as high as 75 cm/yr was observed for the maturing #3 in the present study, while another captive R. typus in Taiwan (67 cm/yr) also grew markedly faster than wild averages (Leu et al.…”
Section: Discussionsupporting
confidence: 71%
“…Annual growth approaching such high rates are only predicted to occur in the wild in young R. typus (e.g., 60 cm/yr at age 1 yr and BL ~ 120 cm), with rates likely declining below 30 cm/yr by age 19 (BL ~ 890 cm; Hsu et al. ). While the growth of the aquarium individuals may not be directly comparable to the observations of Hsu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Female sharks commonly reach maturity at larger sizes than males. Whale shark females smaller than 9.0 m dissected in India [89,90] and South Africa [91] were all immature, while the smallest mature female observed in Taiwan was 9.6 m [92]. Geographic differences in size at maturity have been observed in other shark species [93–95] and may also occur for whale sharks given the information above.…”
Section: Discussionmentioning
confidence: 99%
“…According to length‐at‐age estimates for whale sharks taken in Taiwanese commercial fisheries (Hsu et al . ), Stumpy and Zorro would have been between 14 and 15 years old when first recorded and would be projected to grow ~0.30–0.40 m per year. If correct, this suggests that Stumpy and Zorro are now in their late 30s, yet their growth has been negligible over the past two decades.…”
mentioning
confidence: 99%
“…Citizen science has demonstrated that whale sharks exhibit a high degree of site fidelity, and with longevity conservatively estimated to be at least 80 years (Hsu et al . ), there is the opportunity for this iconic species to be the focus of long‐term natural history studies. The analysis of photographic databases is becoming increasingly popular with citizen scientists, who have gathered information on climate change, invasive species, ecological restoration, and population ecology (Silvertown ).…”
mentioning
confidence: 99%